Collaborating Against Child Abuse Exploring the Nordic Barnahus Model - Johansson, Susanna; Stefansen, Kari; Bakketeig, Elisiv; Kaldal, Anna (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is open access under a CC BY 4.0 license. This edited collection explores the background and implementation of the Nordic Barnahus (or 'Children's House') model - recognised as one of the most important reforms related to children who are the victims of crime in the Nordic region. This book discusses both its potential to affect change and the challenges facing it. The model was introduced as a response to a growing recognition of the need for more integrated and child-centred services for children exposed to violence and sexual abuse. In the Barnahus structure, different professions work together to ensure that victimized children receive help and treatment and that their legal rights are met. This original study is organised into four broad themes: child-friendliness, support and treatment; the forensic child investigative interview; children's rights perspectives; and interagency collaboration and professional autonomy. Each themed section includes in-depth chapters from different Nordic countries, outlining and analysing the practice and outcomes of the collaborative work engaged in by Barnahus from different perspectives. The introductory and concluding chapters offer a comparative lens useful for policy and practice implementation within the Nordic welfare state context and beyond, ensuring this book has global academic and practical appeal.